A novel fatigue assessment approach by Direct Steady Cycle Analysis (DSCA) considering the temperature-dependent strain hardening effect. (February 2019) - Zheng, Xiaotao; Chen, Haofeng; Ma, Zhiyuan; Xuan, Fuzhen
Abstract: A Direct Steady Cycle Analysis (DSCA) method within the Linear Matching Method (LMM) framework is proposed to assess the fatigue life accurately and efficiently for components with arbitrary geometries and cyclic loads. Temperature-dependent stress-strain relationships considering the strain hardening described by the Ramberg-Osgood (RO) formula are discussed and compared with those results obtained by the Elastic-Perfectly Plastic (EPP) model. Additionally, a Reversed Plasticity Domain Method (RPDM) based on the shakedown and ratchet limit analysis method and the DSCA approach within the LMM framework (LMM DSCA) is recommended to design cyclic load levels of Low Cycle Fatigue (LCF) experiments with predefined fatigue life ranges. Based on the ASME code, the material properties at the mean temperature through the wall thickness are used to assess the fatigue life. However, the proposed method can estimate the fatigue life considering the temperature-dependent material properties with strain hardening effect according to the temperature distribution, which is closer to the true operating condition. Graphical abstract: Image 1